2021
DOI: 10.1111/odi.13994
|View full text |Cite
|
Sign up to set email alerts
|

Salivary and gingival CXCL8 correlation with periodontal status, periodontal pathogens, and smoking

Abstract: Recent etiologic models have perceived a central role for neutrophil granulocytes in the manifestation and perpetuation of chronic inflammatory diseases including not only periodontitis, but also rheumatoid arthritis and inflammatory bowel disease (Apel et al., 2018;Colgan, 2015;Jorch & Kubes, 2017). Most importantly, neutrophils have now been recognized to be responsible for the mediation of inflammatory tissue destruction (Rijkschroeff et al., 2018). The severity of periodontitis, as represented by the destr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 66 publications
0
11
0
Order By: Relevance
“…Immunofluorescence analysis detected CXCL8, a core gene in the PPI network, and confirmed that both ZIF-8 and Mino had an effect on the expression of inflammatory factors. Numerous studies have reported significantly increased mRNA and protein levels of CXCL8 in inflammatory gingival tissue sections compared to healthy gingiva . Moreover, CXCL8 levels have shown correlations with clinical indicators of periodontitis, such as bleeding on probing, probing depth, and clinical attachment loss, suggesting an excessive immune response as the primary cause of periodontal tissue destruction .…”
Section: Resultsmentioning
confidence: 99%
“…Immunofluorescence analysis detected CXCL8, a core gene in the PPI network, and confirmed that both ZIF-8 and Mino had an effect on the expression of inflammatory factors. Numerous studies have reported significantly increased mRNA and protein levels of CXCL8 in inflammatory gingival tissue sections compared to healthy gingiva . Moreover, CXCL8 levels have shown correlations with clinical indicators of periodontitis, such as bleeding on probing, probing depth, and clinical attachment loss, suggesting an excessive immune response as the primary cause of periodontal tissue destruction .…”
Section: Resultsmentioning
confidence: 99%
“…CXCL8 is more than an inflammatory cytokine, as it is expressed in healthy periodontal tissues, suggesting its involvement in the permanent need for the periodontium to defend against the microbial burden of the oral cavity [ 10 ]. Moreover, once homeostasis shifts into the pathological stage, CXCL8 becomes a marker of periodontitis [ 8 , 9 , 10 ] and periimplantitis [ 11 ]. The fibroblasts are the primary producers of CXCL8 in periodontitis tissues [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…CXCL8 expression is a double-edged sword: (i) it supports local immunity being constantly expressed at a low level, (ii) or at transient higher levels during wound healing, (iii) however, when chronically expressed at high levels, CXCL8 becomes a key mediator associated with pathological inflammation and overaccentuated neutrophil recruitment and degranulation, overall causing tissue damage [ 7 ]. It is, therefore, not surprising that in healthy periodontal tissues, CXCL8 is regularly expressed to control tissue homeostasis, but CXCL8 is increasingly expressed in the pathological conditions of periodontitis [ 8 , 9 , 10 ] and periimplantitis [ 11 ]. Importantly, evidence suggests that fibroblasts are the primary source of CXCL8 in periodontitis [ 10 ] and periimplantitis [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Saliva is an ideal medium for biomarker discovery due to its non-invasive, safe, and simple collection process, which facilitates repeated sampling with minimal discomfort to the patient (5). Inflammatory mediators, such as Interleukin 6 (IL-6) and Interleukin 8 (IL-8), along with total salivary proteins, are gaining attention as salivary biomarkers because they are closely related to the progression of periodontal disease (2,(6)(7)(8). This interest is based on several studies that have reported elevated levels of these analytes in the saliva of patients with periodontal disease, highlighting their potential usefulness as diagnostic indicators or markers of disease progression (5,9,10).…”
Section: Introductionmentioning
confidence: 99%
“…Interleukin-6 (IL-6) plays a pivotal role in periodontal disease, not only because it is intricately involved in the bone resorption process characteristic of periodontitis but also as a regulator of acute phase proteins in inflammation (9,11). Similarly, Interleukin-8 (IL-8) is crucial for the innate immune response to microorganisms in dental biofilm, facilitating neutrophil recruitment and angiogenesis (6,12). Additionally, the total protein content in saliva is gaining recognition as a promising biomarker.…”
Section: Introductionmentioning
confidence: 99%